The effect of prolonged darkness on the growth, recovery and survival of Antarctic sea ice diatoms - Reeves, S; McMinn, A; Martin, AR (Polar Biology, 2011)
While global climate change in polar regions isexpected to cause significant warming, the annual cycle oflight and dark will remain unchanged. Cultures of threespecies of Antarctic sea ice diatoms, Fragilariopsis cylindrus(Grunow) Krieger, Thalassiosira antarctica Comberand Entomoneis kjellmanii (P.T. Cleve) Poulin and Cardinal,were incubated in the dark and exposed to differingtemperatures. Maximum dark survival times variedbetween 30 and 60 days. Photosynthetic parameters, photosyntheticefficiency (a), maximum quantum yield (Fv/Fm), maximum relative electron transport rate (rETRmax)and non-photochemical quenching (NPQ), showed thatdark exposure had a significant impact on photoacclimation.In contrast, elevated temperatures had a relativelyminor impact on photosynthetic functioning during thedark exposure period but had a considerable impact on darksurvival with minimal dark survival times reduced to only7 days when exposed to 10 Celsius degree. Recovery of maximumquantum yield of fluorescence (Fv/Fm) was not significantlyimpacted by temperature, species or dark exposurelength. Recovery rates of Fv/Fm ranged from -5.06E-7 +- 2.71E-7 s-1 to 1.36E-5 +- 1.53E-5 s-1 formonthly experiments and from -9.63E-7 +- 7.71E-7 s-1to 2.65E-5 +- 2.97E-5 s-1 for weekly experiments. NPQrecovery was greater and more consistent than Fv/Fmrecovery, ranging between 5.74E-7 +- 8.11E-7 s-1 to7.50E-3 +- 7.1E-4 s-1. The concentration of chl-a andmonosaccharides remained relatively constant in bothexperiments. These results suggest that there will probablybe little effect on Antarctic microalgae with increasingwater temperatures during the Antarctic winter.